Clinics in diagnostic imaging (201) - Tan, Timothy Shao Ern (Singapore Med J, 2019)
A 74-year-old woman receiving long-term anticoagulation with warfarin for chronic atrial fibrillation presented with severe acute abdominal pain, diarrhoea and vomiting. Initial laboratory workup revealed a deranged coagulation profile. Computed tomography of the abdomen and pelvis demonstrated spontaneous distal jejunal intramural haematoma with associated reactive ileus. No overt pneumatosis intestinalis, intraperitoneal free gas or haemoperitoneum was seen. Based on clinical and imaging findings, a diagnosis of over-anticoagulation complicated by small bowel intramural haematoma was made. The patient was managed non-operatively with analgesia, cessation of warfarin and reversal therapy with vitamin K. Warfarin therapy was recommenced upon resolution of symptoms and optimisation of coagulation status. The clinical presentation, radiological features and overall management of anticoagulation-induced bleeding are further discussed in this article.